OPTICAL-ELECTRONIC METHOD FOR AEROSOL PARTICLES MEASUREMENT IN ENVIRONMENT - Asatryan, Ruben (International Journal of Research -GRANTHAALAYAH, 2016)
The description of the developed by us automatic Multichannel Aerosol Spectrometer “Masnik-A” are presented. “Masnik-A” system represents the optical/electronic automatic device for measuring of the concentrations and distributions of the sizes of liquid and solid aerosol particles of natural and artificial origin in laboratory and field conditions. Aerosol Spectrometer “Masnik-A” provides a range of measurement of the sizes of aerosol particles from 0.5 up to 40 mm (on a radius). It has 18 channels of the analyzer (graduations by the sizes) with a memory on the channel no less than 9.105 particles. The limiting value of measuring concentrations (containing in 1 cm3 of the aerosol environment) makes no less 2.104 particles. The instrument has possibility of obtaining the command of handle from external personal computer (PC), and also input of the results of measurements for further automatic processing by a specially developed program.